# How to solve 1/x+2/x+2=7/x+5 ?

Welcome to my article 1/x+2/x+2=7/x+5 This question is taken from the simplification lesson.
The solution of this question has been explained in a very simple way by a well-known teacher by doing addition, subtraction, and fractions.
For complete information on how to solve this question 1/x+2/x+2=7/x+5 read and understand it carefully till the end.

Let us know how to solve this question 1/x+2/x+2=7/x+5

First write the question on the page of the notebook,

## 1/x+2/x+2=7/x+5

First of all we will write it properly.

\displaystyle \frac{1}{x}+1+\frac{2}{x}+2=\frac{7}{x}+5

Putting variables together Putting together constant amounts.

\displaystyle \frac{1}{x}+\frac{2}{x}+1+2=\frac{7}{x}+5

Add up the numerators when the denominators are equal,

\displaystyle \frac{{1+2}}{x}+3=\frac{7}{x}+5

\displaystyle \frac{3}{x}+3=\frac{7}{x}+5

Now by translating, we solve by putting the variable amount terms together and the constant amount terms together,

\displaystyle \frac{3}{x}-\frac{7}{x}=5-3

We already know that when the denominators are equal, their numerators are added together.

\displaystyle \frac{{3-7}}{X}=2

\displaystyle \frac{{-4}}{X}=2

The term –4/x can also be written as –4×1/x

Then ,

\displaystyle -4\text{x}\frac{1}{x}=2

Change 1/x to the other side.

\displaystyle -4=2x

then,

\displaystyle -2=x

This article has been completely solved by tireless effort from our side, still if any error remains in it then definitely write us your opinion in the comment box. If you like or understand the methods of solving all the questions in this article, then send it to your friends who are in need.

Note: If you have any such question, then definitely send it by writing in our comment box to get the answer.

## Like the above question, this too will be easily solved.

First of all take it on the copy like this.

\displaystyle \frac{4}{{2x}}+\frac{1}{{2x}}+4+\frac{3}{{2x}}=\frac{7}{{2x}}-5

We know that first we solve by keeping the variable term with the variable term,

keeping the constant term with the constant term.

\displaystyle \frac{4}{{2x}}+\frac{1}{{2x}}+\frac{3}{{2x}}+4=\frac{7}{{2x}}-5

\displaystyle \frac{{4+1+3}}{{2x}}+4=\frac{7}{{2x}}-5

\displaystyle \frac{8}{{2x}}+4=\frac{7}{{2x}}-5

Now we solve by transposing

\displaystyle \frac{8}{{2x}}-\frac{7}{{2x}}=-5-4

Since we know that when the denominators of a term are equal, then their parts are added together.
In this way ,-

\displaystyle \frac{{8+(-7)}}{{2x}}=-9

\displaystyle \frac{{8-7}}{{2x}}=-9

\displaystyle \frac{1}{{2x}}=-9

You can also do lik[ this-

\displaystyle \frac{1}{2}\text{x}\frac{1}{x}=-9

\displaystyle \frac{1}{x}=-9\text{x}2

\displaystyle \frac{1}{x}=-18

\

\displaystyle -\frac{1}{{18}}=x

Example no -2

## how solve 4/x-9+2/x+6=3/x+7?

First let’s write it in simple form,

\displaystyle \frac{4}{x}-9+\frac{2}{x}+6=\frac{3}{x}+7

\displaystyle \frac{4}{x}+\frac{2}{x}-9+6=\frac{3}{x}+7

When the denominators are equal, their parts are added together.

\displaystyle \frac{{4+2}}{x}-3=\frac{3}{x}+7

\displaystyle \frac{6}{x}-3=\frac{3}{x}+7

After this, by translating, we solve by putting the variable amount terms together and the constant amount terms together.
Note – Symbols also change when you transpose.

\displaystyle \frac{6}{x}-\frac{3}{x}=3+7

We know that if the denominators are equal, then their numerators are added together.

\displaystyle \frac{{6+(-3)}}{x}=10[/atex]</p> <p></p> <p> \displaystyle \frac{{6-3}}{x}=10

\displaystyle \frac{3}{x}=10

\displaystyle 3=10x

\displaystyle \frac{3}{{10}}=x